QUALITY OF LIFE OF WOMEN IN REPRODUCTIVE AGE WITH HYPERTENSION - Lia Yulianti; Ermiati Ermiati; Dadang Purnama (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2020)
The rate of hypertension cases in women is higher than in men. Women with reproductive age riskier because of hormonal contraception. Hypertension would cause complications and decreasing the quality of life. The purpose of this study was to determine the quality of life of women with hypertension at Cipanas Garut Health Center. Method: This type of study was quantitative descriptive research. The number of samples was 70 respondents, that chosen using a purposive sampling technique. The instrument in this study was the Indonesian version of the WHOQOLBREF instrument consisting of 26 questions about the quality of life including physical, psychological, social and environmental domains. The data were analyzed as a percentage. This study found that more than half of the respondents' quality of life was in the moderate category (55.8%). The quality of life of women with hypertension was in the moderate category, which means that the quality of life was not good and not bad. However, moral support and health education are needed from health workers about a good lifestyle, regular consumption of antihypertensive drugs, so that blood pressure is controlled so that women have a good quality of life.Keywords: Hypertension, Quality of Life, women of reproductive age.